Matrix Computations of CorwinGreenleaf Multiplicity Functions for Special Unitary Group G = SU (m,n)) - Nasrin, Salma; Nilu, Tanzila Yeasmin; Fardous, Jannatun; Akter, Rubina (Dhaka University Journal of Science, 2015)
In this paper, CorwinGreenleaf multiplicity functions for special unitary group have been studied in the light of the KirillovKostant Theory. This was pioneered by the famous mathematician L. Corwin and F.Greenleaf. The multiplicity function is defined as n(?G?,OH?)=#((OG??pr-1(OG?))/H).In the case where G = SU(m,n), it has been shown that n(OG?,OH?)is at most one Dhaka Univ. J. Sci. 63(2):125-128, 2015 (July)